Sepsis-Induced Immunosuppression Is Marked by an Expansion of a Highly Suppressive Repertoire of FOXP3+ T-Regulatory Cells Expressing TIGIT. (11th August 2021) - de Lima, Mikhael Haruo Fernandes; Hiroki, Carlos Hiroji; de Fátima Borges, Vanessa; Cebinelli, Guilherme Cesar Martelossi; Santos, Jessica; Rosa, Marcos Henrique; Silva, Camila Meirelles S; Wanderley, Carlos Wagner S; Gonçalves, Augusto Velozo; Quirino, Gustavo Fernando Silva; Zamboni, Dario S; Cunha, Thiago M; et al.
Abstract: Background: Although the literature shows that an increase in both the number and suppressive function of CD4 + forkhead box P3 (FOXP3) + T-regulatory cells (Tregs) during sepsis contributes to an immunosuppressed state, little is known about the identity of these cells. Methods: Using the sepsis mouse model of cecal ligation and puncture (CLP), we analyzed the frequency and molecular signature of the T-cell immunoglobulin and ITIM domain (TIGIT) + and TIGIT − Treg subsets, using flow cytometry and quantitative polymerase chain reaction. In addition, ST2 −/− and signal transducer and activator of transcription 6 (STAT6) −/− mice were submitted to CLP or recombinant interleukin 33 (IL-33) treatment to investigate the mechanism whereby TIGIT + Tregs differentiate during sepsis. Results: Sepsis was marked by the sustained expansion of the highly suppressive TIGIT + Treg subset, which expresses Helios, neuropilin 1, and high levels of Tnfrsf18 and Pdcd1 at 15 days after CLP. The increase in TIGIT + Tregs was accompanied by higher susceptibility to nosocomial bacteria challenge, suggesting their association with post sepsis immunosuppression. Mechanistically, we found that the ST2 deletion abrogated the expansion of the TIGIT + Treg subset during sepsis. Furthermore, treatment with recombinant IL-33 resulted in the expansion of TIGIT + Tregs depending on the STAT6 and M2 macrophages. Conclusions: These findings demonstrated that only the TIGIT + Tregs remain stably expanded at the late phase of sepsis. Moreover, the expansion of TIGIT + Tregs is dependent on the IL-33/ST2/STAT6/M2 macrophage axis. Abstract : The routes related to expansion of the T-cell immunoglobulin and ITIM domain (TIGIT) + T-regulatory cell repertoire are still unknown. Our study demonstrates that interleukin 33 is pivotal in selectively expanding this repertoire in a STAT6 and M2 macrophage–dependent fashion.